Simulation of cosmo balls in wastewater treatment - Hussain, Siti Aslina; Tan, Hong Tat; Idris, Azni (2012)
There are multiple ways to have wastewater treated. Being the common is the aeration tank where wastewater is captured in a tank for certain duration which known as Hydraulic Retention Time and it is then aerated. The aeration process pumps air into the wastewater by means of using surface aerator devices or using air diffusers which are install at the bottom of the tank. Cosmo ball serves as a packing medium in the aeration tank to allow microbial to growth on its surface. The air pumped into the wastewater provides the microbial with the oxygen need for oxidation of organic matter. Hence, the distribution of the oxygen around the Cosmo balls is crucial in determining the efficiency of the wastewater treatment plant. The purpose of this simulation is to have an insight on the flow distribution of the wastewater with and without the air across the Cosmo balls transient state. The Cosmo ball in bulk serves as the restriction to the flow. The multiphase flow show significant mixing in the system where the fine bubble serves as virtual mixer in the wastewater. In addition, the zone of the bubble retain in the system will improve the overall efficiency of the treatment plant. This is due to the fact that the bacteria will have sufficient contact time with the air bubble for oxidation process to occur. For a single Cosmo ball, it was found that the velocity distributed uniformly in the intermediate flow region while at the turbulence region the velocity is higher (Hussain et al., 2010). The lag in the individual Cosmo ball flow indicates that the hollow region in the balls can induce higher retention time for wastewater treatment. This is due to the nature of the chaotic flow regime inside the hollow region. The efficiency of the wastewater treatment plant greatly improves as well as to reduce the area needed for the treatment (Hussain et al., 2010). As can be seen in Figure 1(a), the air volume fraction is estimated at 0.1 due to great dispersion of the air bubble. For Figure l(b) and l(c) shows that air volume fraction is estimated at 0.15 and 0.20, respectively. This is due to less air bubble concentrate around the Cosmo balls in wastewater treatment tank. As a result, the higher the volume fraction the lower the concentration of air bubble distribute across the Cosmo ball as illustrated in Figure led), lee) and l(!) which is the volume fraction at 0.25, 0.30 and 0.35, respectively. This is significantly agreed due to air bubble unifonniy distributed across the Cosmo ball causing the microbial in the wastewater obtain oxygen unifonniy. This phenomenon is good in improving the wastewater treatment efficiency as most of the air volume fraction concentrate at about lower O.LIt is to be noted that most of the bubble will be trapped in either the internal volume of Cosmo ball or at the fin side of the Cosmo ball. This can greatly enhance the oxygen transfer rate to the wastewater as the bubble have enough retention time in the wastewater and exchange the required gas with the microbial on the surface of the Cosmo ball. This is agreed with the result found by Hussain et al., 2010. This is due to the bubble collision or break-up near to Cosmo ball surface and tank wall as shown in Figure 2. At high enough mixture velocity, the flow ultimately becomes mix (dispersion of air in water or water in air), but this is achieve only slowly. The effect of the high velocity show the tendency of the flow to mix and approach uniform distribution as the flow proceeds towards to the top of the tarue are the key of the result as depicted in Figure 2. The result proved that at higher velocity, the flow tendency to mix and distributed uniformly as found by Hussain et al., 2010. In general the streamline result illustrate the great complexity of liquid-gas disperse flow, reflecting to turbulence, gravitation, bubble break-up and coalesces which are occurring in the tank.